Resolvin D1 ameliorates Inflammation-Mediated Blood-Brain Barrier Disruption After Subarachnoid Hemorrhage in rats by Modulating A20 and NLRP3 Inflammasome - Wei, Chengcong; Guo, Shenquan; Liu, Wenchao; Jin, Fa; Wei, Boyang; Fan, Haiyan; Su, Hengxian; Liu, Jiahui; Zhang, Nan; Fang, Dazhao; Li, Guangxu; Shu, Shixing; et al. (Frontiers in Pharmacology, 2021)
Inflammation is typically related to dysfunction of the blood-brain barrier (BBB) that leads to early brain injury (EBI) after subarachnoid hemorrhage (SAH). Resolvin D1(RVD1), a lipid mediator derived from docosahexaenoic acid, possesses anti-inflammatory and neuroprotective properties. This study investigated the effects and mechanisms of RVD1 in SAH. A Sprague-Dawley rat model of SAH was established through endovascular perforation. RVD1was injected through the femoral vein at 1 and 12 h after SAH induction. To further explore the potential neuroprotective mechanism, a formyl peptide receptor 2 antagonist (WRW4) was intracerebroventricularly administered 1 h after SAH induction. The expression of endogenous RVD1 was decreased whereas A20 and NLRP3 levels were increased after SAH. An exogenous RVD1 administration increased RVD1 concentration in brain tissue, and improved neurological function, neuroinflammation, BBB disruption, and brain edema. RVD1 treatment upregulated the expression of A20, occludin, claudin-5, and zona occludens-1, as well as downregulated nuclear factor-κBp65, NLRP3, matrix metallopeptidase 9, and intercellular cell adhesion molecule-1 expression. Furthermore, RVD1 inhibited microglial activation and neutrophil infiltration and promoted neutrophil apoptosis. However, the neuroprotective effects of RVD1 were abolished by WRW4. In summary, our findings reveal that RVD1 provides beneficial effects against inflammation-triggered BBB dysfunction after SAH by modulating A20 and NLRP3 inflammasomes.